Additive manufacturing and high performance applications - Lindgren, Lars-Erik (2018)
The requirement on life and robustness for aero-engine components poses obstacles to additive manufacturing. It is expected that increasing knowledge about the process and thereby its development together with adaption of existing alloys may improve this state. Simulations can contribute to understanding as well as be used in the design of process and components in order to reduce residual deformations and stresses as well as defects. Models for the latter are still not well established. The paper describes various existing approaches and also on-going developments at Luleå University of Technology that enable better descriptions in the near weld region for crack initiation.